Youtube as a Medium for Distributing the Philosophy of Science: The Peak of Goodness is in Love - Elya Afifah Yusuf; Kun Wazis; Siti Raudhatul Jannah; Dwi Ayu Wulandari; Indah Pramitha Sari (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Through his YouTube account, the uploaded content is very interesting to listen to and has an implicit message in the YouTube channel